SISTEM INFORMASI PENGELOLAAN KEGIATAN PENGAJIAN ANTARA MAGHRIB DAN ISYA (STUDI KASUS : KELURAHAN PENYENGAT RENDAH KOTA JAMBI ) - Suana, Irma; Reza Yolanda, Adelia (LP2M Universitas Nurdin Hamzah, 2023)
The current problem is the reporting of data on maghrib and isha recitation activities and the non-exposure of maghrib and isha recitation activities to the wider community so that many people do not know the maghrib and isha recitation activities. To design a web-based information system so that data processing can be effective, efficient and computerized that can be used by the data processing of Maghrib and Isya Studies Teachers (PAMI) in Penyengat Low Village to facilitate the process of managing teacher data. The research approach used by the author is qualitative research. The system development method used by the author is the waterfall model. The information system is designed using Visual Studio Code tools and uses PHP programming language with Codeigniter framework and uses MySQl database. For this reason, the Jambi City Low Stinger Subdistrict Office, specifically in the Social Welfare Office, really needs a tool that is more efficient and effective in managing data on maghrib and isya recitation activities by inputting data and displaying reports that can be printed out. With the design of this system, the Social Welfare Office is helped in the process of obtaining information about teacher data, mosque data, activity data, RT data, and student data. In making an information system design application for data management of maghrib and isya activities of Penyengat Low Village Jambi City, the author uses the Visual Studio Code application with PHP programming language for designing the application.